2022
DOI: 10.1111/cpr.13352
|View full text |Cite
|
Sign up to set email alerts
|

ATF7‐dependent epigenetic changes induced by high temperature during early porcine embryonic development

Abstract: Background: Activating transcription factor 7 (ATF7) is a member of the ATF/cAMP response element (CRE) B superfamily. ATF2, ATF7, and CRE-BPa are present in vertebrates. Drosophila and fission yeast have only one homologue: dATF2 and Atf1, respectively. Under normal conditions, ATF7 promotes heterochromatin formation by recruiting histone H3K9 di-and tri-methyltransferases. Once the situation changes, all members are phosphorylated by the stress-activated kinase P38 in response to various stressors. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…We found that heat stress does not drive the release of Atf1 from heterochromatin ( Figure 3A ), instead the binding affinity between Atf1 and heterochromatin protein Swi6 HP1 is severely compromised ( Figures 4A and 9 ). This is distinct from the cases in Drosophila , mouse and swine, where the release of phosphorylated Atf1 homologs dATF-2 or ATF7 from heterochromatin is the major cause of the disrupted heterochromatin at elevated temperatures ( Liu et al, 2019 ; Seong et al, 2011 ; Sun et al, 2023 ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We found that heat stress does not drive the release of Atf1 from heterochromatin ( Figure 3A ), instead the binding affinity between Atf1 and heterochromatin protein Swi6 HP1 is severely compromised ( Figures 4A and 9 ). This is distinct from the cases in Drosophila , mouse and swine, where the release of phosphorylated Atf1 homologs dATF-2 or ATF7 from heterochromatin is the major cause of the disrupted heterochromatin at elevated temperatures ( Liu et al, 2019 ; Seong et al, 2011 ; Sun et al, 2023 ).…”
Section: Discussionmentioning
confidence: 67%
“…TERRA can be transgenerationally transmitted to zygotes via sperm and causes telomere shortening in the offspring ( Liu et al, 2019 ). During early porcine embryonic development, high temperatures also trigger the increased expression level of p38, which leads to ATF7 phosphorylation, heterochromatin disruption, and eventually the failure of blastocyst formation ( Sun et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that heat stress does not drive the release of Atf1 from heterochromatin (Figure 3A), instead the binding affinity between Atf1 and heterochromatin protein Swi6 HP1 is severely compromised (Figure 4A and 8). This is distinct from the cases in Drosophila, mouse and swine, where the release of phosphorylated Atf1 homologues dATF-2 or ATF7 from heterochromatin is the major cause of the disrupted heterochromatin at elevated temperatures (Liu et al, 2019;Seong et al, 2011;Sun et al, 2023).…”
Section: Instability Of Atf/creb Family Protein-dependent Temperature...mentioning
confidence: 65%
“…Although the possible impact of the environment on epigenetic regulation has attracted considerable interest, it remains largely unknown how environmental cues bring about epigenetic fluctuations. So far, sporadic studies have demonstrated that heat stress is one of the most prevalent environmental stresses that trigger epigenetic alterations, which may negatively affect early embryonic development in mammals (Sun et al, 2023) and eye colour-controlling gene inactivation during early larval development in Drosophila (Seong et al, 2011), or serve as thermosensory input to positively control the rate of vernalization of the flowering plants after winter (Antoniou-Kourounioti et al, 2018;Feil and Fraga, 2012;Song et al, 2013).…”
Section: Introductionmentioning
confidence: 99%